GO / ADN / GAP-ETPE compound, preparation method and application

By introducing graphene oxide and ammonium dinitamide into GAP-ETPE, the GO/ADN/GAP-ETPE complex was prepared, which solved the shortcomings of GAP-ETPE in terms of explosion, combustion and safety performance, and achieved significant improvement in performance.

CN119552040APending Publication Date: 2025-03-04XIAN MODERN CHEM RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411868958.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing polyazide glycidyl ether-based energy-containing thermoplastic elastomers (GAP-ETPEs) have shortcomings in explosion, combustion and safety performance, especially in terms of poor explosion and combustion performance and high impact sensitivity.

Method used

By introducing graphene oxide (GO) and ammonium dinitamide (ADN) into GAP-ETPE, the GO/ADN/GAP-ETPE complex was prepared, and the amount of GO and ADN was added was changed to improve the explosion, combustion and safety performance of GAP-ETPE.

Benefits of technology

It significantly improves the explosion and combustion heat of GAP-ETPE, reduces the impact sensitivity, thereby improving its explosion, combustion and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195260460000021
    Figure BDA0005195260460000021
  • Figure BDA0005195260460000022
    Figure BDA0005195260460000022
  • Figure BDA0005195260460000023
    Figure BDA0005195260460000023
Patent Text Reader

Abstract

The invention provides a GO / ADN / GAP-ETPE compound as well as a preparation method and application thereof. The compound is prepared from graphene oxide, ammonium dinitramide and a glycidyl azide polymer-based energetic thermoplastic elastomer through a solvent evaporation method. The average molecular weight of the glycidyl azide polymer based energy-containing thermoplastic elastomer is 20000 to 30000; the mass ratio of the graphene oxide to the ammonium dinitramide to the glycidyl azide polymer based energy-containing thermoplastic elastomer is 1: (3-8): (90-200). According to the GO / ADN / GAP-ETPE compound prepared by the invention, the explosion heat and the combustion heat of the original GAP-ETPE can be improved, the explosion heat is improved by 105.9 J / g-532.1 J / g, the combustion heat is improved by 297.9 J / g-354.7 J / g, and the impact sensitivity of the GAP-ETPE can be reduced from 9J to 36J-50J.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energetic materials, and in particular relates to a graphene oxide (GO) / ammonium dinitramide (ADN) / glycidyl polyazide based energetic thermoplastic elastomer (GAP-ETPE) composite, a preparation method and an application thereof. Background Art

[0002] Energetic thermoplastic elastomer (ETPE) as a solid propellant binder can give the propellant advantages such as high energy, insensitivity, low characteristic signal and recyclability. Azide-based energetic thermoplastic elastomers have the advantages of large heat release, no need for oxygen consumption during decomposition, and good compatibility with nitramine explosives, which have attracted widespread attention. Among them, polyazide glycidyl ether (GAP)-based ETPE is the representative. Solid propellants based on GAP-ETPE binders have become a research hotspot for thermoplastic elastomer propellants. However, due to the high carbon content of the GAP-ETPE chain, its explosion and combustion properties are poor, which affects the explosion and combustion properties of the GAP-ETPE binder formulation. In addition, GAP-ETPE contains more azide groups (-N 3 ), resulting in a high impact sensitivity, affecting its safety performance. Lu Tingting et al. added graphene oxide to GAP-ETPE in the patent "A method for preparing a graphene oxide / GAP-ETPE composite" (authorization number: ZL202010886215.3), and improved the thermal stability of the original GAP-ETPE and lowered the glass transition temperature of the original GAP-ETPE. However, the carbon content of graphene oxide is also high. After adding it, it cannot improve the explosion heat and combustion heat of GAP-ETPE. Summary of the invention

[0003] The invention provides a graphene oxide (GO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite, a preparation method and an application thereof. GO and ADN are introduced into GAP-ETPE to prepare the composite. Without changing the structure of GAP-ETPE, the explosion, combustion and safety performances of GAP-ETPE are improved by changing the addition amounts of GO and ADN.

[0004] In order to achieve the above technical tasks, the present invention adopts the following technical solutions:

[0005] A GO / ADN / GAP-ETPE composite is prepared by using graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer through a solvent volatilization method; the average molecular weight of the polyazide glycidyl ether-based energetic thermoplastic elastomer is 20000-30000; and the mass ratio of graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:(3-8):(90-200).

[0006] Optionally, the mass ratio of the graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:5:100.

[0007] Optionally, the molecular structure of the GAP-ETPE is as follows:

[0008]

[0009] Where 30≤a, b, c≤45, and a, b and c are all integers.

[0010] Optionally, the molecular structure of the GO is as follows:

[0011]

[0012] Optionally, the molecular structure of the raw material ADN is as follows:

[0013]

[0014] The method for preparing any of the GO / ADN / GAP-ETPE composites of the present invention comprises the following steps:

[0015] Step 1: GO is dispersed and dissolved in tetrahydrofuran to obtain a GO dispersion, and the amount ratio of GO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g;

[0016] Step 2: GAP-ETPE is dissolved in tetrahydrofuran to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g;

[0017] Step 3: ADN is added to N-methylpyrrolidone to obtain an ADN solution, wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g;

[0018] Step 4: GO dispersion and GAP-ETPE clear solution are mixed to obtain a mixed solution of GO and GAP-ETPE;

[0019] Step 5: The ADN solution is dropped into the mixed solution of GO and GAP-ETPE under stirring, and the mixture is evenly mixed, and the composite is obtained after standing and drying.

[0020] Optionally, the solutions prepared in steps 1-3 are stirred at a temperature range of 20 to 35° C. for 1 to 2 hours.

[0021] Optionally, in step 4, the mixed solution is stirred at 20-40° C. for 0.5-1 h.

[0022] Optionally, the dropping temperature in step 5 is 20-40° C., and after the dropping is completed, the system is stirred for 0.5-1 h, left to stand at room temperature for 1-2 weeks, and dried at 30-40° C. for 2-4 h to obtain the composite.

[0023] Application of any GO / ADN / GAP-ETPE composite of the present invention in preparing a solid propellant adhesive.

[0024] Compared with the prior art, the present invention has the following beneficial technical effects:

[0025] The prepared GO / ADN / GAP-ETPE composite of the present invention can increase the explosion heat and combustion heat of the original GAP-ETPE, the explosion heat is increased by 105.9 J / g to 532.1 J / g, the combustion heat is increased by 297.9 J / g to 354.7 J / g, and the impact sensitivity of GAP-ETPE can be reduced from 9 J to 36 J to 50 J. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0027] Figure 1 is a SEM image of the raw material GAP-ETPE composite prepared in Example 1 of the present invention;

[0028] Figure 2 This is a SEM image of the GO / ADN / GAP-ETPE composite prepared in Example 1 of the present invention.

[0029] Figure 3 This is the IR graph of the raw material GAP-ETPE composite prepared in Example 1 of the present invention;

[0030] Figure 4 This is the IR graph of the GO / ADN / GAP-ETPE composite prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following detailed description of the present invention is exemplary and does not limit the scope of the present invention. Based on the embodiments of the present invention, for ordinary technicians in the field, all uncreative improvements should be considered as the protection scope of the present invention without departing from the present invention.

[0032] The present invention provides a graphene oxide (GO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite and a preparation method thereof, belonging to the technical field of energetic materials. ADN (chemical name: ammonium dinitramide) is a new type of high-energy green oxidant composed of ammonium cations and dinitramide anions, and is one of the typical representatives of the third generation of energetic materials. It has high density (1.82 g / cm 3 ), high oxygen coefficient (2.0), low sensitivity, clean fuel gas (halogen-free), etc., representing the international advanced level of high-energy oxidizers. Compared with the common oxidizer ammonium perchlorate (AP), ADN has a higher formation enthalpy (ADN: -1208kJ / kg, AP: -2782kJ / kg), a smaller average relative molecular mass of fuel gas (ADN: 26, AP: 31), and the theoretical specific impulse of ADN-based solid propellants with the same mass content is 3s to 10s higher than that of AP-based solid propellants, representing the international advanced level of today's high-energy propellants. It can be added to GAP-ETPE together with graphene oxide to improve its explosion, combustion and safety performance.

[0033] The molecular structure of GO is not unique and can be shown as follows:

[0034]

[0035] The molecular structure of the raw material ADN is as follows:

[0036]

[0037] The molecular structure of the raw material GAP-ETPE is as follows:

[0038]

[0039] Where 30≤a, b, c≤45, and a, b and c are all integers.

[0040] The preparation method of the graphene oxide (GO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite of the present invention does not need to change the structure of GAP-ETPE, can directly improve the explosion, combustion and safety performance of GAP-ETPE, has high reaction efficiency and low production cost.

[0041] The method uses GO, ADN and GAP-ETPE as raw materials, and comprises the following steps: adding GO into tetrahydrofuran and subjecting to ultrasound; adding GAP-ETPE into tetrahydrofuran and stirring; adding ADN into N-methylpyrrolidone and stirring; pouring GO dispersion into a mixed solution of GAP-ETPE and tetrahydrofuran and stirring; dropping ADN solution into the mixed solution of GO and GAP-ETPE, stirring evenly, and standing at room temperature for 1 to 2 weeks to obtain a graphene oxide / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite. The prepared GO / ADN / GAP-ETPE composite of the present invention can increase the explosion heat and combustion heat of the original GAP-ETPE, the explosion heat is increased by 105.9 J / g to 532.1 J / g, the combustion heat is increased by 297.9 J / g to 354.7 J / g, and the impact sensitivity of GAP-ETPE can be reduced from 9 J to 36 J to 50 J.

[0042] The preparation method specifically comprises the following steps:

[0043] Step 1, adding GO to tetrahydrofuran, and ultrasonically dispersing it at a temperature range of 20 to 35° C. for 1 to 2 hours, wherein the amount ratio of GO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g;

[0044] Step 2, adding GAP-ETPE to tetrahydrofuran, stirring for 1 to 2 hours at a temperature range of 20 to 35° C., filtering out insoluble matter, and obtaining GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g;

[0045] Step 3, adding ADN to N-methylpyrrolidone, stirring for 1 to 2 hours at a temperature range of 20 to 35° C., and waiting for ADN to be completely dissolved to obtain an N-methylpyrrolidone solution of ADN; wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g;

[0046] Step 4, pouring the GO dispersion obtained in step 1 into the mixed solution of GAP-ETPE and tetrahydrofuran obtained in step 2, stirring the system at 20-40° C. for 0.5-1 h, and obtaining a mixed solution of GO and GAP-ETPE after the solution is uniform;

[0047] Step 5, adding the N-methylpyrrolidone solution of ADN obtained in step 3 dropwise to the mixed solution of GO and GAP-ETPE obtained in step 4 under stirring, wherein the dropping temperature is 20-40°C, stirring the system for 0.5-1h after the dropping is completed, and after stirring evenly, standing at room temperature for 1-2 weeks, and drying at 30-40°C for 2-4h to obtain the corresponding graphene oxide (GO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite.

[0048] As a two-dimensional carbon nanostructured material, graphene oxide has attracted much attention in the fields of nanocomposites, sensors, hydrogen storage capacitors and batteries. Graphene oxide has extremely high mechanical properties, good biocompatibility, superior electron transport capacity and excellent electrochemical properties, making it an ideal compound for improving the mechanical properties of materials.

[0049] Among the raw materials involved in the present invention, the graphene oxide raw material is purchased through the distributor Beijing Bailingwei Technology Co., Ltd. Ammonium dinitramide (ADN) is provided by the Xi'an Modern Chemistry Research Institute, and the impact sensitivity is 9J. Polyazide glycidyl ether (GAP), with a relative molecular weight of 3000, is a commercially available product of the Xi'an Modern Chemistry Research Institute. The polyazide glycidyl ether-based energetic thermoplastic elastomer GAP-ETPE in the raw materials of the present invention is prepared according to the method disclosed in the document "Preparation and Properties of GAP-ETPE / NC Blended Polymers", Energetic Materials, 24(4):331-335. The relative molecular weight of GAP-ETPE is 20000-30000, the explosion heat is 1826.6J / g, the combustion heat is 21758.9J / g, and the impact sensitivity is 9J.

[0050] Embodiment 1:

[0051] 60 mg GO was added to 150 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 1.5 h, 6.0 g GAP-ETPE was added to 200 g tetrahydrofuran, stirred at 25 ° C for 1.5 h, until GAP-ETPE was completely dissolved; 0.3 g ADN was added to 50 g N-methylpyrrolidone, stirred at 25 ° C for 1.5 h, until ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 30 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 30 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 35 ° C for 3 h to obtain 6.0 g of the corresponding graphene oxide (GO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite. The explosion heat of the GO / ADN / GAP-ETPE composite is 2358.7 J / g, which is 532.1 J / g higher than that of GAP-ETPE. The combustion heat is 22113.6 J / g, which is 354.7 J / g higher than that of GAP-ETPE. The impact sensitivity is 50 J, which is 41 J higher than that of GAP-ETPE.

[0052] Structural analysis

[0053] (1) Scanning electron microscopy (SEM) analysis

[0054] Figure 1 This is the SEM image of the raw material GAP-ETPE prepared in Example 1. Figure 2 This is a SEM image of the GO / ADN / GAP-ETPE composite prepared in Example 1. The surface morphology of GAP-ETPE and its composite was studied using a scanning electron microscope and it was found that pure GAP-ETPE was relatively smooth, and when GO and ADN were added, the GAP-ETPE composite became relatively rough, and ADN and GO could be seen, while GAP-ETPE was coated on top.

[0055] (2) Infrared analysis

[0056] Figure 3 This is the IR graph of the raw material GAP-ETPE prepared in Example 1. Figure 4 This is the IR image of the GO / ADN / GAP-ETPE composite prepared in Example 1. From the infrared image, it can be seen that the GO / ADN / GAP-ETPE composite has a wavelength of 3057 cm -1 (NH 4 + ), 1618cm -1 (NO 2 ) and 1278cm -1 (NO 2) The characteristic peaks of ADN appeared. The characteristic peaks of GO, such as hydroxyl, carbonyl, alkoxy and other functional groups, are also found in GAP-ETPE.

[0057] Embodiment 2:

[0058] 10 mg GO was added to 20 g tetrahydrofuran, ultrasonically dispersed at 20 ° C for 1.5 h, 1.3 g GAP-ETPE was added to 150 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.06 g ADN was added to 25 g N-methylpyrrolidone, stirred at 20 ° C for 1 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 35 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 1 week, it was dried at 40 ° C for 2 h to obtain 4.2 g of the corresponding GO / ADN / GAP-ETPE composite. The explosion heat of the GO / ADN / GAP-ETPE composite is 1932.5 J / g, the combustion heat is 22066.8 J / g, and the impact sensitivity is 38 J.

[0059] Embodiment 3:

[0060] 18 mg GO was added to 20 g tetrahydrofuran, ultrasonically dispersed at 22 ° C for 1.5 h, 3.0 g GAP-ETPE was added to 160 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.09 g ADN was added to 15 g N-methylpyrrolidone, stirred at 20 ° C for 1 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 30 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 40 ° C for 2 h to obtain 4.7 g of the corresponding GO / ADN / GAP-ETPE composite. The explosion heat of the GO / ADN / GAP-ETPE composite is 2147.8 J / g, the combustion heat is 22086.7 J / g, and the impact sensitivity is 40 J.

[0061] Embodiment 4:

[0062] 26 mg GO was added to 40 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 1 h, 5.1 g GAP-ETPE was added to 120 g tetrahydrofuran, stirred at 24 ° C for 1.5 h, and GAP-ETPE was completely dissolved; 0.15 g ADN was added to 30 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 30 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 30 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 30 ° C for 3 h to obtain the corresponding GO / ADN / GAP-ETPE composite 5.0 g. The explosion heat of the GO / ADN / GAP-ETPE composite is 2209.4 J / g, the combustion heat is 22107.1 J / g, and the impact sensitivity is 45 J.

[0063] Embodiment 5:

[0064] 31 mg GO was added to 80 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 1.5 h, 5.3 g GAP-ETPE was added to 150 g tetrahydrofuran, stirred at 20 ° C for 1.5 h, and GAP-ETPE was completely dissolved; 0.19 g ADN was added to 40 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 35 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 20 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 35 ° C for 2 h to obtain the corresponding GO / ADN / GAP-ETPE composite 5.3 g. The explosion heat of the GO / ADN / GAP-ETPE composite is 2000.7 J / g, the combustion heat is 22089.1 J / g, and the impact sensitivity is 48 J.

[0065] Embodiment 6:

[0066] 40 mg GO was added to 110 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 2 h, 5.6 g GAP-ETPE was added to 180 g tetrahydrofuran, stirred at 20 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.22 g ADN was added to 35 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 30 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 1 week, it was dried at 30 ° C for 4 h to obtain the corresponding GO / ADN / GAP-ETPE composite 5.5 g. The explosion heat of the GO / ADN / GAP-ETPE composite is 2144.3 J / g, the combustion heat is 22105.4 J / g, and the impact sensitivity is 38 J.

[0067] Embodiment 7:

[0068] 46 mg GO was added to 130 g tetrahydrofuran, ultrasonically dispersed at 32 ° C for 1 h, 5.7 g GAP-ETPE was added to 160 g tetrahydrofuran, stirred at 22 ° C for 1.5 h, until GAP-ETPE was completely dissolved; 0.27 g ADN was added to 40 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, until ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 24 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 35 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 1 week, it was dried at 30 ° C for 3 h to obtain the corresponding GO / ADN / GAP-ETPE composite 5.6 g. The explosion heat of the GO / ADN / GAP-ETPE composite is 2248.6 J / g, the combustion heat is 22043.7 J / g, and the impact sensitivity is 44 J.

[0069] Embodiment 8:

[0070] 52mgGO was added to 110gtetrahydrofuran, ultrasonically dispersed at 27℃ for 1h, 4.8gGAP-ETPE was added to 170gtetrahydrofuran, stirred at 26℃ for 1h, until GAP-ETPE was completely dissolved; 0.29gADN was added to 35gN-methylpyrrolidone, stirred at 20℃ for 1h, until ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 33℃ for 1h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 36℃, stirred for 1h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, the corresponding GO / ADN / GAP-ETPE composite 4.7g was obtained by drying at 34℃ for 2h. The explosion heat of the GO / ADN / GAP-ETPE composite is 2311.8 J / g, the combustion heat is 22088.9 J / g, and the impact sensitivity is 39 J.

[0071] Embodiment 9:

[0072] 55 mg GO was added to 100 g tetrahydrofuran, ultrasonically dispersed at 27 ° C for 2 h, 5.9 g GAP-ETPE was added to 160 g tetrahydrofuran, stirred at 24 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.17 g ADN was added to 40 g N-methylpyrrolidone, stirred at 20 ° C for 2 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 36 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 30 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 30 ° C for 3 h to obtain the corresponding GO / ADN / GAP-ETPE composite 4.8 g. The explosion heat of the GO / ADN / GAP-ETPE composite is 2199.7 J / g, the combustion heat is 22108.4 J / g, and the impact sensitivity is 46 J.

[0073] Embodiment 10:

[0074] 27 mg GO was added to 80 g tetrahydrofuran, ultrasonically dispersed at 30 ° C for 1.5 h, 4.3 g GAP-ETPE was added to 120 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.20 g ADN was added to 30 g N-methylpyrrolidone, stirred at 25 ° C for 2 h, and ADN was completely dissolved; GO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and GO at 25 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 30 ° C for 2 h to obtain 4.2 g of the corresponding GO / ADN / GAP-ETPE composite. The explosion heat of the GO / ADN / GAP-ETPE composite is 1994.8 J / g, the combustion heat is 22075.1 J / g, and the impact sensitivity is 39 J.

[0075] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A GO / ADN / GAP-ETPE composite, characterized in that: The composite is prepared by using graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer through a solvent volatilization method; The average molecular weight of the polyazide glycidyl ether-based energetic thermoplastic elastomer is 20,000 to 30,000; The mass ratio of graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:(3-8):(90-200).

2. The GO / ADN / GAP-ETPE composite according to claim 1, characterized in that: The mass ratio of the graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:5:

100.

3. The GO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of the GAP-ETPE is shown below: Where 30≤a, b, c≤45, and a, b and c are all integers.

4. The GO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of GO is shown below:

5. The GO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of the raw material ADN is as follows:

6. The method for preparing the GO / ADN / GAP-ETPE composite according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: GO is dispersed and dissolved in tetrahydrofuran to obtain a GO dispersion, and the amount ratio of GO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g; Step 2: GAP-ETPE is dissolved in tetrahydrofuran to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g; Step 3: ADN is added to N-methylpyrrolidone to obtain an ADN solution, wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g; Step 4: GO dispersion and GAP-ETPE clear solution are mixed to obtain a mixed solution of GO and GAP-ETPE; Step 5: The ADN solution is dropped into the mixed solution of GO and GAP-ETPE under stirring, and the mixture is evenly mixed, and the composite is obtained after standing and drying.

7. The method for preparing the GO / ADN / GAP-ETPE composite according to claim 6, characterized in that: The solutions prepared in steps 1-3 are all stirred at a temperature range of 20 to 35° C. for 1 to 2 hours.

8. The method for preparing the GO / ADN / GAP-ETPE composite according to claim 6, characterized in that: In the step 4, the mixed solution is stirred at 20-40° C. for 0.5-1 h.

9. The method for preparing the GO / ADN / GAP-ETPE composite according to claim 6, characterized in that: The dropping temperature in step 5 is 20-40° C. After the dropping is completed, the system is stirred for 0.5-1 h, left to stand at room temperature for 1-2 weeks, and dried at 30-40° C. for 2-4 h to obtain the composite.

10. Use of the GO / ADN / GAP-ETPE composite according to any one of claims 1 to 5 for preparing a solid propellant adhesive.

Citation Information

Patent Citations

  • A method for preparing a graphene oxide / GAP-ETPE composite

    CN112028725B